Nonextensive statistics and the finite-volume QCD phase transition - Ahmed, M. A.A.; Zainuddin, H. (Elsevier B.v., 2026)
Recent studies have increasingly applied Tsallis nonextensive statistics to Quantum Chromodynamics (QCD) to account for deviations from thermal equilibrium. Within this framework, the Tsallis parameter q characterizes long-range interactions, non-Markovian memory, and multifractal boundary effects; it links directly to temperature variances in fluctuating systems, which vanish in the Boltzmann-Gibbs limit. This study investigates the thermodynamic variables of a hot and dense system using the QCD MIT bag model, employing the Tsallis distribution to describe thermal response functions related to the equation of state. We focus on the deconfinement phase transition from a hadron gas to a Partonic Plasma to analyze the behavior of key thermodynamic quantities, such as energy and entropy densities, pressure, isothermal compressibility, and the interaction measure at finite volume. Furthermore, we examine the influence of the q-parameter on the phase transition point. Our findings reveal that the transition point is significantly shifted by the q-parameter, highlighting the importance of nonextensive statistics in characterizing the system’s thermal evolution.